IMPROVING LAYOUT DESIGN TO MINIMIZE DEFECT STOCKS IN PT. XYZ - Hasanudin, Mochamad; Adhi Utama, Akbar (Journal of Business and Management, 2017)
Abstract. Defect problem is an important issue that happens in the warehouse as it can be the result of minimizing the profit of the company. PT. XYZ, one of the companies that have the large warehouse for supporting their business operation have a defect problem in their warehouse. PT XYZ is a company that produces fertilizer on a large scale, the market is one of the provinces in Java and the main product of PT XYZ is Urea Fertilizer. During the year 2016, the company suffers 12,100 tons defect stock of urea fertilizer or equal to 1.3% from their total production. This research aims to analyze the effects of the defect problem, find the cause of the problem and develop the possible solution to improve or minimize the defect stock problem in the warehouse of PT. XYZ based on the operational management theory. After the Data collected from several of observation and interview, then the effect from defect problem was identified that is adding salary of employees, adding machine costs, the loss from disposal of broken sacks, and the loss from disposal of unfeasible fertilizers. The total cost and loss resulted from this effects are amounted to Rp. 807,340,000. The root cause analysis was conducted to find the core cause of the problem. In this research, Current Reality Tree tool was used to find the root cause. After passing through the several phases then got the cause of the stock defect that is less optimum design layout on the warehouse in PT XYZ. The possible solution that has been made is to re-design the warehouse layout at PT XYZ because it is related to the problem of causing stock defect and need to be evaluated. In redesigning the layout, the researcher using the framework of previous research. Step by step is done according to the framework that has been made and in the last step, a warehouse layout was created as a proposed solution to the company.Keywords: Defective Stock, Root Cause Analysis, Warehouse Design Framework, Warehouse Layout Design